DETERMINAN PERSALINAN SECTIO CAESAREA DI RS SYAFIRA KOTA PEKANBARU TAHUN 2018 - Novita, Diana; S, Donel; Nurlisis, Nurlisis (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
Caesarean delivery is a fetal birth by performing an incision on the abdominal/laparotomy and uterine/hysterotomy. The proportion of caesarean deliveries in the city of Pekanbaru continues to increase both in government hospitals and private hospitals. Syafira Hospital is a private hospital with the highest proportion of caesarean deliveries from six other private hospitals in the city of Pekanbaru. Data from January to December 2017 the number of caesarean deliveries was 495 (56.4%) from 877 deliveries. The aim of this research is to know the determinant factors of delivery of caesarean at Syafira Hospital in Pekanbaru City. This study uses quantitative observational analytical method with design case control.This research was conducted from August to September 2018. Using secondary data collection, from medical records. The population consisted of cases and controls, with a sample of 203 cases of caesarean section delivery and 203 normal delivery controls. Data analysis was carried out in univariate, bivariate and multivariate with multiple logistic regression using prediction models. The results of the study revealed that determinant factors were maternal medical indications at risk 35 times for delivery by caesarean (95% CI = 12,970-95,924).It is advisable for the hospital to promote the advantages and disadvantages of each type of childbirth, the use of antenatal care for early detection of labor complications, and to optimize the role of health workers in the handling of maternal neonatal emergencies.